2015
DOI: 10.1016/j.molcel.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Basal Transcription Complex Component TAF3 Transduces Changes in Nuclear Phosphoinositides into Transcriptional Output

Abstract: SummaryPhosphoinositides (PI) are important signaling molecules in the nucleus that influence gene expression. However, if and how nuclear PI directly affects the transcriptional machinery is not known. We report that the lipid kinase PIP4K2B regulates nuclear PI5P and the expression of myogenic genes during myoblast differentiation. A targeted screen for PI interactors identified the PHD finger of TAF3, a TATA box binding protein-associated factor with important roles in transcription regulation, pluripotency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 60 publications
4
65
0
Order By: Relevance
“…C2C12 cells depleted of endogenous TAF3 were reconstituted with either wild type or mutant KK-TAF3 and then PIP4K2B was knocked down. The data clearly demonstrate that the expression of a subset of PIP4K2B-regulated myogenic genes requires the intact phosphoinositide interacting PHD finger of TAF3 [46]. Similar results were observed for PtdIns5P-mediated regulation of gene expression by the PHD finger containing protein ING2 (inhibitor of growth protein 2) under conditions of stress [55].…”
Section: Nuclear Turtles and Taf3 Promote Muscle Differentiationsupporting
confidence: 77%
See 2 more Smart Citations
“…C2C12 cells depleted of endogenous TAF3 were reconstituted with either wild type or mutant KK-TAF3 and then PIP4K2B was knocked down. The data clearly demonstrate that the expression of a subset of PIP4K2B-regulated myogenic genes requires the intact phosphoinositide interacting PHD finger of TAF3 [46]. Similar results were observed for PtdIns5P-mediated regulation of gene expression by the PHD finger containing protein ING2 (inhibitor of growth protein 2) under conditions of stress [55].…”
Section: Nuclear Turtles and Taf3 Promote Muscle Differentiationsupporting
confidence: 77%
“…In a recent study 17 out of 32 different PHD fingers tested interacted with phosphoinositides [46]. Phosphoinositide interaction was not associated with any other function of PHD fingers such as H3K4me3 interaction and was observed with PHD fingers derived from proteins that function as writers, erasers and readers [46]. These data suggest that nuclear Phosphoinositides are likely to play a significant role in regulating chromatin conformation and transcriptional output.…”
Section: Knowing Your Turtle's Friends Illuminates the Pathwaymentioning
confidence: 93%
See 1 more Smart Citation
“…Dissection of the C-terminal domains of Yng2 showed that it contains a PHD motif followed by a frequently associated polybasic region (PBR). Other PHD/PBRcontaining proteins, such as ING2, Pf1, and TAF3, have been shown to bind phosphoinositides (phosphatidylinositol biphosphate or phosphatidylinositol triphosphate), and this binding is important for phospholipid-dependent nuclear signaling and gene expression, arguably through cross talk with recognition of H3K4 by the PHD (58)(59)(60)(61)(62). In order to evaluate the function and the biochemical properties of these domains, we generated mutants with mutations in these two regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One example of the latter scenario is the STAR-PAP poly-A RNA polymerase that uses PtdIns-4,5-P 2 as essential cofactor (23,24). Other examples include direct modification of a phosphoinositide bound to the nuclear receptor by inositide multikinase kinase (25,26) and control of the basal transcription machinery by nuclear phosphoinositides (27).…”
Section: Implications For Nuclear Pl Signalingmentioning
confidence: 99%